Surface properties of CrN coated engine cylinders - Oner, Cengiz; Hazar, Hanbey; Nursoy, Mustafa (Elsevier Sci Ltd, 2009)
In an experimental study performed on a single cylinder four stroke diesel engine, the cylinder was coated with CrN by PVD and its surface behaviors were investigated. The wear behaviors of the engine with CrN coated cylinder and with uncoated, cast iron, cylinder were compared. The effect of hardness, surface topography, microstructure, and running conditions were studied. With X-ray analysis, the structural changes on the surface due to thermal and mechanical shocks were examined. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Thermal Barrier Coatings; Plasma-Sprayed Coatings; Behavior; Wear; Pvd